Estudo da relação entre domínio tecnológico, interação e aprendizagem "colaborativa" na EaD on-line pelo uso de um modelo de equações estruturais. - Silva, Andréa Soares Rocha da (2009)
Although distance learning is not a recent educational model, its new format, which has been modernized with the insertion of information and communication technologies, especially the computer and the Internet, has brought resources that enable interaction at a higher level, totally modifying its function and potential results. Motivated by these new functionalities and potentialities, which the use of computer and Internet has brought, this Doctoral Dissertation has as its objective to test a hypothesized model involving the relation between technological expertise, interaction and collaborative learning from an online distance learning course. In order to achieve this objective, as a pioneer initiative in that research area, the analyses were carried out through the application of structural equations modeling which confirmed the existence of a triple relation between student technical practice, teacher-student and student-student interactions and collaborative learning process. The general model showed acceptable goodness of fit as well as the structural equations showed significant coefficients, the construct reliabilities were quite high and R2 exhibits good explanation power of the endogenous variables. It has been observed also the frequent use of the internet and communication tools (such MSN, Yahoo Messenger, among others) made available through e-mails and chat-rooms – for discussion, along with other communication tools, such as, those which have directly influenced the technological advances of online distance learning students, making this technological expertise absolutely necessary for a good development of an online distance learning course. It has been noticed the interactions between teacher-student and student-student through the communication tools and collaborative activities characterize the interactions that occur in online distance learning, and contribute effectively in the learning process of students in this type of learning environment. At the end it is emphasized that the students who have mastered an adequate technological capacity will have the ability to acquire a more strong interaction which will consequently influence and bring positive impact to their learning in an online course.